1994
DOI: 10.1002/eji.1830240423
|View full text |Cite
|
Sign up to set email alerts
|

CD3 components at the surface of pro‐T cells can mediate pre‐T cell development in vivo

Abstract: Developmentally arrested pro-T cells (CD4-8-, IL-2R+, HSA++) of RAG-1-deficient mice appear to express low levels of CD3 molecules in the absence of T cell receptor (TcR) chains at their surface, while developmentally arrested pre-T cells of TcR alpha-deficient mice express low levels of a disulfide-linked TcR beta chain in association with CD3 molecules. Cross-linking of the CD3 modules on pro-T cells of RAG-1-/- mice in vivo, with either of two different CD3 epsilon-specific monoclonal antibodies, induces di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 39 publications
6
92
0
Order By: Relevance
“…2B). In Rag-deficient mice, where T cell development is arrested at the DN3 stage, injecting anti-CD3 mAb has been shown to mimic pre-TCR signaling: It overcomes the developmental block, increases thymic cellularity, allows DN3 cells to differentiate into DN4 and then subsequently to the DP stage, but not to SP stages [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…2B). In Rag-deficient mice, where T cell development is arrested at the DN3 stage, injecting anti-CD3 mAb has been shown to mimic pre-TCR signaling: It overcomes the developmental block, increases thymic cellularity, allows DN3 cells to differentiate into DN4 and then subsequently to the DP stage, but not to SP stages [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…We therefore decided to use the RT3 (RAG2-/-treated with anti-CD3 4 antibody [18]) mouse as our routine model for such a purpose: the stimulation of the CD3 4 molecule expressed at the surface of immature triplenegative (TN) RAG2-/-thymocytes bypasses the requirement for a TCR g chain and allows the T cell differentiation program to reach the double-positive (DP) step where the TCR § rearrangements should occur if the recombinase was efficient. Nine days after in vivo injection of anti-CD3, RT3 thymocytes form a phenotypically homogenous population of CD4 + CD8 + DP cells in which the TCR § locus is accessible yet unrearranged, as shown by strong TEA expression [19].…”
Section: Global Chromatin Accessibility Of the Tcr > Locus Prior To Rmentioning
confidence: 99%
“…In addition, studies in the normal human thymus (19) and in acute lymphoblastic leukemias (20,21) have also demonstrated the presence of CD3 e protein in immature T cells, although the exact stage of development was not determined. Finally, biochemical studies have shown that CD3 e, y and 8 (in the presence or absence of TCR P chains), may be detected on the surface of SCID thymocytes (22), SCID cell lines (23) and RAG-I"'" thymocytes (24), all of which are principally of the CD44 l0 CD25 + DN phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of RAG"'" thymocytes with anti-CD3e mAb, either in vivo (24,25) or in vitro (26), induces expansion and differentiation of CD44 k) CD25 + DN cells to the DP stage in the absence of TCR rearrangement. RAG"'" or SCID thymocytes can also be induced to expand and differentiate to the DP stage under the influence of either a TCR P transgene (24,27,28) or a pSG^ transgene (29). Taken together, these results in both normal and mutant mice provide strong evidence for the presence of at least some components of the TCR-CD3 complex on immature thymocytes.…”
Section: Introductionmentioning
confidence: 99%